(z-12)(z+12)=0

Simple and best practice solution for (z-12)(z+12)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (z-12)(z+12)=0 equation:


Simplifying
(z + -12)(z + 12) = 0

Reorder the terms:
(-12 + z)(z + 12) = 0

Reorder the terms:
(-12 + z)(12 + z) = 0

Multiply (-12 + z) * (12 + z)
(-12(12 + z) + z(12 + z)) = 0
((12 * -12 + z * -12) + z(12 + z)) = 0
((-144 + -12z) + z(12 + z)) = 0
(-144 + -12z + (12 * z + z * z)) = 0
(-144 + -12z + (12z + z2)) = 0

Combine like terms: -12z + 12z = 0
(-144 + 0 + z2) = 0
(-144 + z2) = 0

Solving
-144 + z2 = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '144' to each side of the equation.
-144 + 144 + z2 = 0 + 144

Combine like terms: -144 + 144 = 0
0 + z2 = 0 + 144
z2 = 0 + 144

Combine like terms: 0 + 144 = 144
z2 = 144

Simplifying
z2 = 144

Take the square root of each side:
z = {-12, 12}

See similar equations:

| 500x=200(2-x) | | (2j+7)(2j-7)=0 | | 4x+18-3x=8+4x-5 | | (ab+3)(ab-3)=0 | | -6-3x=5x+16 | | y=-2(x+1)-7 | | (x-1)(x-2)(x-3)=0 | | (n-1)*6=36 | | h(t)=-5t^2+10t+3 | | 13+9x=x | | x^2+8x+15=0 | | (2x+9)(x+1)=0 | | a*6+3=15 | | x(x+7)+5(x+7)=0 | | H(t)=64t-16t^2 | | 17x-8=3x+18 | | 3x-(4x-13)=11 | | (j+7)(k-5)=0 | | 14k=-2747 | | 6m-(31m-18)=12(m-11)+3m | | -9-6x=16 | | 3|5=x|27 | | 4+6n=n+9 | | 8ln(x)=-5 | | 6x+12=-13 | | (a+8)(b+3)=0 | | 2sin(x)= | | 24x+12=(12x+6) | | 19.50x-20=-55 | | 11+8ln(x)=6 | | 4+4x=7+2x | | lnx=0.04 |

Equations solver categories